Further Reflections on the Stylistic Aspects of Syntax in the Context of Contemporary Developments in Linguistics - Jędrzejko, Ewa (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article aims to emphasise the need for scholars to return to the idea of developing a coherent theory of stylistic grammar, a concept postulated long ago by numerous linguists who anticipated the possibilities that such a theory could potentially open. Recalling some of the more important factors determining the nature of today’s linguistics, the study presents an overview of the major directions in research on the style-generating functions of syntax in texts representing various types and genres. It also indicates the key sources of inspiration for such studies. Existing works (both theoretical and analytical) provide solid foundations for attempts to develop a modern theory of stylistic syntax, a theory capable of accounting for a wide variety of dimensions of text/discourse.